Collaborative Research in Economics in Pakistan: The Case of Pakistan Development Review from 1973 to 2009 - Jan, Sajjad Ullah; Anwar, Mumtaz A. (Qualitative and Quantitative Methods in Libraries; 2015: Special Issue: Bibliometrics, 2017)
The patterns of collaborative authorship (extent of international collaboration and degree of collaboration) and institutional affiliation in the papers of the Pakistan Development Review were determined by using bibliometric techniques. The sample used was the papers published during 1973-2009. Of the 1627 papers, 723 (44.44%) were the result of collaborative effort. International collaboration was observed only in 94 papers. The degree of collaboration was 0.44 as whole and the year-wise calculated degree ranged between 0.13 and 0.76. The year 2009 was the most productive year in terms of collaborative research.